Experimental and numerical study on ultra low cycle fatigue fracture of X steel tubular joints with CHS braces to SHS chord. (May 2021) - Huang, Xuewei; Wei, Chenchen; Zhou, Jiajia; Zhao, Jun; Ge, Jianzhou
Abstract: Steel tubular joints in steel structures may suffer from ultra low cycle fatigue fracture under strong seismic action. This paper aims to investigate the ultra low cycle fatigue behavior of X steel tubular joints with CHS braces to SHS chord by means of experiments and numerical simulation. Firstly, three X-joints with different constructions were tested. The experimental results indicate that the X-joint with fillet weld or penetration weld exhibits punching failure mode, and the weld forms have no obvious effect on the deformation ability and fatigue life of the joint. As for the X-joint with internal stiffener in the chord, it shows tensile fracture failure characteristic and has low deformation capacity, and there is no obvious surface crack before sudden fracture failure. Afterwards, the fracture failure of the X-joints were numerically simulated by using the cyclic void growth model. It shows that the crack growth rate is greatly underestimated by the model, and the predicted fatigue life of the X-joints was obviously longer than that of the tests, thus the evaluation on fatigue life of X-joints tended to be unsafe. A Lode parameter enhanced cyclic void growth model (referred to as LCVGM) was thus developed to consider shear effect on the fracture prediction, and the LCVGM parameters of base metal and weld metal were determined based on the experimental results of the pure shear specimens. Finally, the LCVGM was applied to simulate the ultra low cycle fatigue fracture of the X-joints, and it is shown that the model can well predict the whole fracture process and fatigue life of the joints. Highlights: ULCF loading tests were conducted on three X-joints with different welding construction. The loading and deformation capacity of the X-joints were compared in the test. A Lode parameter enhanced cyclic void growth model was presented. Fracture process of steel tubular joints under ultra low cyclic loading was simulated. The LCVGM shows better accuracy in fracture prediction of the X-joints than the CVGM.